The influence of joint positioning of the osoto-gari sweeping leg on muscle force potential of the gastrocnemius - Imamura, R. T.; Iteya, M.; Parker, D. L. (Association for the Scientific Studies on Judo, Kodokan, 2017)
The results o f the study indicate that experienced judoka prefer to position their ankle in plantarflexion rather than dorsiflexion, during the downward motion of the osoto-gari sweep. This is consistent with previous research that found vigorous plantarflexion activity with experienced judoka (Imamura and Johnson, 2003; Narazaki et al. 2007; Imamura et al. 2011). In terms of gastrocnemius muscle length and force production, the results indicate that, black beit, judoka do not, position their joints in a position for optimal force production. According to concepts established by Crawford and James (1980), the gastrocnemius shoulcl create the greatest, amount, of force during a neutral muscle "resting length. That, said, a plantarflexed position o f the ankle will create a shortening o f the muscle and, therefore, warrant, a lengthening response at, the knee (i.e. knee extension). This was not, demonstrated in this study. While not, significantly different, from novice, black beit, subjects actually depicted greater knee flexion angles. Thus, black beit, judoka under these conchtions are actually at, a disadvantage in terms of potential gastrocnemius muscle force production.